2023
DOI: 10.1186/s12909-023-04864-3
|View full text |Cite
|
Sign up to set email alerts
|

Dental hygiene and dental students’ motivations for future work: a cross-sectional study of first-year students at a dental hygiene school and a dental school in Japan

Yasuyuki Takahashi,
Asami Iguchi,
Shiho Motoi
et al.

Abstract: Background It is important to understand the career motivations and perceptions of students who intend to become dental health professionals. Both dental and dental hygiene students may have different opinions about the profession and future work prospects. To our knowledge, no study has compared the career motivations and career perceptions of Japanese dental and dental hygiene students after admission to dental or dental hygiene school. This cross-sectional study examined the motivations of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…As previous studies on the impact of gender differences on career choice have shown, females were less concerned with the financial component of a career and more concerned with care and human factors [ 7 , 21 , 22 ]. It could be said that females prefer this career because they believe that the nature of dentistry allows them to effectively balance their personal and professional lives [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies on the impact of gender differences on career choice have shown, females were less concerned with the financial component of a career and more concerned with care and human factors [ 7 , 21 , 22 ]. It could be said that females prefer this career because they believe that the nature of dentistry allows them to effectively balance their personal and professional lives [ 23 ].…”
Section: Discussionmentioning
confidence: 99%